Treatment paradigm and prognostic factor analyses of rectal squamous cell carcinoma - Liu, Rui; Zhang, Jiahui; Zhang, Yinjie; Yan, Jin (Frontiers in Oncology, 2023)
Background: Rectal squamous cell carcinoma (rSCC) is a rare pathological subtype of rectal cancer. There is no consensus on the treatment paradigm for patients with rSCC. This study aimed to provide a paradigm for clinical treatment and develop a prognostic nomogram. Methods: Patients diagnosed with rSCC between 2010 and 2019 were identified in the Surveillance, Epidemiology, and End Results (SEER) database. According to the TNM staging system, Kaplan‒Meier (K-M) survival analysis was used to identify the survival benefits of different treatments in patients with rSCC. The Cox regression method was used to identify independent prognostic risk factors. Nomograms were evaluated by Harrell's concordance index (C-index), calibration curves, decision curve analysis (DCA) and K-M curves. Results: Data for 463 patients with rSCC were extracted from the SEER database. Survival analysis showed that there was no significant difference in cancer-specific survival (CSS) among patients with TNM stage 1 rSCC treated with radiotherapy (RT), chemoradiotherapy (CRT) or surgery (P = 0.249). In TNM stage 2 patients, there was a significant difference in CSS among those treated with surgery, RT, and CRT (P = 0.003). In TNM stage 3 patients, there was a significant difference in CSS among those treated with CRT, no treatment and CRT plus surgery (P < 0.001). In TNM stage 4 patients, there was a significant difference in CSS among those treated with CRT, chemotherapy (CT) and no treatment (P = 0.041). Cox regression analysis showed that age, marital status, T stage, N stage, M stage, PNI, tumor size, RT, CT, and surgery were independent risk factors for CSS. The 1-, 3-, and 5-year C-indexes were 0.877, 0.781, and 0.767, respectively. The calibration curve showed that the model had excellent calibration. The DCA curve showed that the model had excellent clinical application value. Conclusion: RT or surgery is recommended for patients with stage 1 rSCC, and CRT is recommended for patients with stage 2, stage 3, and stage 4 rSCC. Age, marital status, T stage, N stage, M stage, PNI, tumor size, RT, CT, and surgery are independent risk factors for CSS in patients with rSCC.